Developing Writing Competence through Culturally Responsive Pedagogy in Multilingual Nepal - Thapa, Hukum (KMC Journal, 2025)
Nepal’s secondary classrooms are rich in linguistic and cultural diversity. However, traditional writing instruction frequently overlooks students’ lived experiences and multilingual backgrounds. In this regard, this study examines how culturally responsive pedagogy (CRP) can enhance writing competence by integrating students’ home languages, local knowledge, and cultural narratives into classroom practices. The purpose is to assess the impact of CRP-based strategies on students’ writing skills, engagement, and sense of identity. Drawing on pilot interventions conducted in three districts, the study involved classroom observations, teacher interviews, and analysis of student writing samples. Learners participated in writing tasks that encouraged the use of their mother tongues and community storytelling traditions. Results show that students produced more coherent, expressive, and structurally diverse texts. Teachers also reported a shift toward more interactive and meaningful writing instruction, leading to increased student motivation and participation. The findings demonstrate that CRP not only improves grammatical accuracy and genre understanding but also fosters a deeper sense of ownership and confidence in writing. The study concludes by emphasizing the need for curriculum and policy reforms that recognize linguistic diversity and cultural heritage as essential resources for effective writing instruction.